-2(3x-4)+3(5x-1)=

Simple and best practice solution for -2(3x-4)+3(5x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x-4)+3(5x-1)= equation:


Simplifying
-2(3x + -4) + 3(5x + -1) = 0

Reorder the terms:
-2(-4 + 3x) + 3(5x + -1) = 0
(-4 * -2 + 3x * -2) + 3(5x + -1) = 0
(8 + -6x) + 3(5x + -1) = 0

Reorder the terms:
8 + -6x + 3(-1 + 5x) = 0
8 + -6x + (-1 * 3 + 5x * 3) = 0
8 + -6x + (-3 + 15x) = 0

Reorder the terms:
8 + -3 + -6x + 15x = 0

Combine like terms: 8 + -3 = 5
5 + -6x + 15x = 0

Combine like terms: -6x + 15x = 9x
5 + 9x = 0

Solving
5 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 9x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 9x = 0 + -5
9x = 0 + -5

Combine like terms: 0 + -5 = -5
9x = -5

Divide each side by '9'.
x = -0.5555555556

Simplifying
x = -0.5555555556

See similar equations:

| -5x+7=3x-5 | | 6+3x=8+-14 | | x^5-4x^4-32x^3= | | w+2.75=13.13 | | .24=log(x) | | 4-(x-5)=3(x-11) | | [5x]=10 | | 18-2x=x+19 | | q-1.53=7.04 | | 4.33b=495 | | r+1=7.85 | | 4=-8n | | 13x-3=5x-6 | | 6(x-9)=-30 | | 4.33=495 | | 6+-7=8 | | 16x-3=7x+6 | | 4(36+9y)=-72 | | -7/83/4 | | 4r-6-3=4r-9 | | a(z+5)=32 | | 4x-13=3x-1 | | d−8/−2=12 | | 4(x+6)=3x+4 | | c+3=3(11-3c) | | 6.1=u-3.3 | | x+5y=4z | | 1/2(1/4) | | -9x-6=6x+9 | | 5/4t=10 | | -24=3/4j | | 2.5=g-7 |

Equations solver categories